STRATEGI GURU PAI DALAM MEMBENTUK KARAKTER RELIGIUS SISWA KELAS IX SMP SWASTA IT AL MUNADI MEDAN PROVINSI SUMATERA UTARA - Fatiha Setya Ningtyas; Fakhrurrozi Fakhrurrozi; Candra Gunawan (Journal of Islamic Religious Education, 2026)
This study aims to analyze in depth the strategies of Islamic Religious Education (PAI) teachers in shaping the religious character of ninth-grade students at SMP Swasta IT Al Munadi Medan, North Sumatra Province. This research uses a descriptive qualitative approach with data collection techniques including participatory observation, in-depth interviews, and documentation. The research informants consisted of the principal, PAI teachers, and ninth-grade students. Data analysis was carried out through data reduction, data display, and systematic conclusion drawing. The results show that PAI teachers apply comprehensive strategies including role modeling, habituation of worship, contextual learning strategies, emotional and spiritual approaches, religious motivation, value-based assignments, religious extracurricular activities, collaboration with parents, and discipline enforcement. These strategies effectively shape students' religious character reflected in politeness, honesty, responsibility, social awareness, and discipline in worship. Keywords: PAI Teacher Strategy, Religious Character, Islamic Education